Analysis of national chemistry olympiad in Costa Rica: achievements and challenges for young people - Rocío Madrigal, Ana (2012)
The School of Chemistry has promoted programs and academic projects, such as the Chemistry Olympiad that stimulates and enhances learning of science. Competition identified students with high academic performance and promotes selfimprovement opportunities for healthy and stimulating scientific thinking. After more than a decade, data has been compiled and organized to statistically analyze of the first 10 years using SPSS 11.5. This article includes statistical analysis for each of the issues, including variability and significance. The information is presented in schematic form, considering variables such as gender, geographic location of educational institutions and modality. A significant difference was obtained between men and women (T = 2.961, P < 0.03 eliminatory test, category A) and (T = 3.640, P < 0.00 qualifying grades, category A). A similar pattern was obtained in the modality of education and geographic location. Quantitatively demonstrates the growing interest and enthusiasm for participation. It’s been more than 10 years, and the Chemistry Olympiad in Costa Rica is a consolidated program, high credibility nationally and internationally that outlines future scientists in fields related to natural sciences.